THE CONFLUENCE OF SCIENCE AND ARTISTIC INSPIRATION IN GYÖRGY LIGETI’S MUSICAL THINKING - Attila FODOR (Studia Universitatis Babeş-Bolyai. Musica)
Original and contradictory, György Ligeti’s work is rooted in a complex creative thought, influenced by several innated and personal factors. In this context premature affinity towards the natural sciences, the passion for music, and other qualities like synesthesia and a generalized artistic sensitivity proved to be definitive. He manifested during his an opened attitude towards (almost all kind of) music, though his output is basically dominated by several – extremely personal – dichotomies, which ultimately demonstrate a fundamental duality of his personality: science-art, craft-intuition, calculus-emotion, presence-distance, mechanic-kaleidoscopic, grotesque-absurd, manipulation-ecstasy. Our study tries to find out the roots of these dichotomies, mainly through his writings and memories.